Multi-environmental evaluation of barley core collection against spot blotch for genetic variability and identification of promising genotypes exhibiting resistance - Shiv Shankar Patel; Shyam Saran Vaish; Sherry Rachel Jacob; Gyanendra Pratap Singh; Vikender Kaur (BMC Plant Biology)
Abstract Background Spot blotch caused by Bipolaris sorokiniana (Sacc.) Shoemaker significantly impedes global barley production by impacting grain, fodder yield, and malt quality. Host resistance presents a sustainable, cost-effective, and eco-friendly method for disease management. The extent of resistance and the number of resistant accessions are limited within barley genetic resources. Therefore, the present studies on the evaluation of the selected barley core collection consisting of 678 genotypes under the multi-environmental conditions have paramount importance. To identify stable resistance resources, the trial was conducted at Varanasi, India. This location is known as the hot spot of spot blotch. Results The analysis of variance (ANOVA) for determining varying levels of spot blotch resistance among the examined genotypes revealed a significant genotypic variation among the accessions against the disease based on the area under the disease progress curve (AUDPC). After correlating the disease severity with the elevated minimum temperatures and humidity levels, it was found to be higher during the first cropping season (2021–2022) with a mean AUDPC value of 852.89 ± 6.48 over the second cropping season (2022–2023) that showed a mean AUDPC of 761.10 ± 6.78. Average AUDPC scores across four test environments revealed that none of the evaluated genotypes showed a completely resistant reaction (AUDPC < 285) to spot blotch. Two genotypes (EC0667513-sel and EC0667512-sel) of six-row barley exhibited moderately resistant (MR) reaction (AUDPC < 355) under the natural field conditions; however, among these two, only EC0667513-sel was found to be MR during the validation under the artificial epiphytotic conditions. Further comparison of the performance and stability among these two MR genotypes through GGE biplot analysis indicated that EC0667512-sel was specifically adapted to certain environments, but was inconsistent overall. In contrast, EC0667513-sel indicated a good mean performance and higher stability across all environments. Conclusion The GGE biplot effectively analyzed genotype-environment interactions and identified optimal evaluation sites and stable resistant genotypes for spot blotch resistance. These findings provide valuable insights for future breeding programs focused on integrating resistance traits into new barley varieties.